An Analysis of the Qanun Aceh within the Framework of the Qur’anic Maqāṣid in the Unitary State of the Republic of Indonesia - Ahmad Miftahun Ni'am; Afifah Mayaningsih (Academica: Journal of Multidisciplinary Studies, 2026)
Despite the constitutional recognition of Aceh’s special autonomy, scholarly debates persist regarding the compatibility of Aceh’s Qanun regulations with the broader legal and ideological framework of the Unitary State of the Republic of Indonesia (NKRI), particularly when assessed through Qur’anic normative principles. This study aims to examine the extent to which the implementation of Qanun in Aceh Province aligns with the framework of the Maqāṣid al-Qur’an while remaining consistent with the foundational principles of the Indonesian state. Using a qualitative library research approach, this study analyzes legal documents, regional regulations, and scholarly works related to the Qanun, with particular attention to regulations concerning Islamic criminal law, Islamic financial institutions, and educational governance. The analysis focuses on how these regulations function in promoting public welfare, justice, and social order within Acehnese society. The findings reveal that the Qanun of Aceh generally reflects the objectives of the Maqāṣid al-Qur’an, particularly in safeguarding public interests, strengthening moral and social responsibility, and supporting community-based development. Although challenges remain, especially regarding human rights discourse and legal harmonization, the Qanun continues to operate within the constitutional framework of the NKRI. This study contributes to the discourse on Islamic law and constitutional pluralism in Indonesia by demonstrating that regionally based Sharī’a regulations can coexist with national legal systems and serve as a model of local wisdom that reinforces national unity rather than undermining it.